Nonterminating Extensions of the Sears Transformation - Chu, Wenchang; Li, Nadia N. (Sarajevo Journal of Mathematics, 2024)
By means of two and three term relations of _3φ_2-series, we investigate the nonterminating _4φ_3-series. Eight transformation formulaes into double series are established. Four of them are shown to be nonterminating extensions of the Sears transformation.